2011
DOI: 10.1039/c1dt10290g
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic and thermodynamic study of the unexpected comproportionation reaction between cis-[OsVIIIO4(OH)2]2− and trans-[OsVIO2(OH)4]2− to form a postulated [OsVIIO3(OH)3]2− complex anion

Abstract: A kinetic study of [OsO(4)] reduction by aliphatic alcohols (MeOH and EtOH) was performed in a 2.0 M NaOH matrix at 298.1 K. The rate model that best fitted the UV-VIS data supports a one-step, two electron reduction of Os(VIII) (present as both the [Os(VIII)O(4)(OH)](-) and cis-[Os(VIII)O(4)(OH)(2)](2-) species in a ratio of 0.34:0.66) to form the trans-[Os(VI)O(2)(OH)(4)](2-) species. The formed trans-[Os(VI)O(2)(OH)(4)](2-) species subsequently reacts relatively rapidly with the cis-[Os(VIII)O(4)(OH)(2)](2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 37 publications
5
26
0
3
Order By: Relevance
“…(15)] durch Gerber und Mitarbeiter [38] Schwefeldioxid diente zur Modellierung der CO-Komplexierung an Rhodium-und Iridium-Hydroformylierungskatalysatoren. (15)] durch Gerber und Mitarbeiter [38] Schwefeldioxid diente zur Modellierung der CO-Komplexierung an Rhodium-und Iridium-Hydroformylierungskatalysatoren.…”
Section: Leicht Zu Beobachtende Assoziationen: üBergangsmetalle Und Lunclassified
See 2 more Smart Citations
“…(15)] durch Gerber und Mitarbeiter [38] Schwefeldioxid diente zur Modellierung der CO-Komplexierung an Rhodium-und Iridium-Hydroformylierungskatalysatoren. (15)] durch Gerber und Mitarbeiter [38] Schwefeldioxid diente zur Modellierung der CO-Komplexierung an Rhodium-und Iridium-Hydroformylierungskatalysatoren.…”
Section: Leicht Zu Beobachtende Assoziationen: üBergangsmetalle Und Lunclassified
“…Eine Untersuchung der Oxidation von Alkoholen mit OsO 4 in Gegenwart von Natriumhydroxid [Gl. (15)] durch Gerber und Mitarbeiter [38] Schwefeldioxid diente zur Modellierung der CO-Komplexierung an Rhodium-und Iridium-Hydroformylierungskatalysatoren. [41] Salaita et al [42] verwendeten die MCV, um zu zeigen, dass Schwefeldioxid und ein Rhodium(I)-Carbonyl-Komplex in kurzen Reaktionszeiten einen beobachtbaren 1:1-Komplex ergaben [Gl.…”
Section: Leicht Zu Beobachtende Assoziationen: üBergangsmetalle Und Lunclassified
See 1 more Smart Citation
“…A full kinetic analysis showed that this highly reactive intermediate is indeed present in low concentrations, which precludes structural characterization, but it is definitely the species that is in the center of the catalytic activity. A formal kinetic scheme is proposed to interpret the kinetic findings with the full consideration of the various labile equilibria of osmium(VIII) species in aqueous solution …”
Section: Introductionmentioning
confidence: 99%
“…A formal kinetic scheme is proposed to interpret the kinetic findings with the full consideration of the various labile equilibria of osmium(VIII) species in aqueous solution. [29][30][31][32] 2 | EXPERIMENTAL…”
Section: Introductionmentioning
confidence: 99%